Islamic Economics in Manado: Identity Negotiation of Muslim Minorities in a Multicultural Society - Luntajo, Mohammad Muzwir Rusliansyah; Jankauskienė, Dainora; Babangida, Bala (Potret Pemikiran, 2024)
Islamic economics has emerged as a significant alternative financial system in recent decades. In Manado, as a region with a Muslim minority, Islamic economic practices demonstrate unique dynamics within a multicultural society context. This research aims to analyze how Islamic economics functions as an identity negotiation mechanism for the Muslim minority in Manado, focusing on identifying integration success factors, stakeholder roles, and formulating an adaptive development model. Using qualitative methods with a literature study approach enriched by spontaneous observations, this research reveals three main findings. First, the successful integration of Islamic economic practices is supported by universal value recognition, market-based adaptation, and social capital development. Second, stakeholders' active role in Islamic economic adaptation and development is manifested through inclusive leadership, cross-cultural business partnerships, and multicultural understanding promotion. Third, an adaptive Islamic economic development model has been successfully formulated with key components including an inclusive economic framework, multi-stakeholder collaboration, and cultural integration mechanisms. These findings indicate that Islamic economics can develop sustainably in plural societies through local context adaptation.